19. PREVALENCE AND ASSOCIATED FACTORS OF NON-SPECIFIC VAGINITIS AT NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY (Vietnam Journal of Community Medicine, 2025)
Objective: Identify the prevalence and associated factors of non-specific vaginitis in women undergoing gynecological examination at the National Hospital for Obstetrics and Gynecology from June 2024 to February 2025.Subject: A total of 300 women aged 18-49 who undergoing gynecological examination at the National Hospital for Obstetrics and Gynecology were included in the study. All participants underwent interviews, gynecological examinations, and microscopic examination of vaginal discharge. Patients were diagnosed with non-specific vaginitis based on the Nugent criteria.Study methods: A prospective descriptive study.Results: The prevalence of non-specific vaginitis was 37.6%. Most affected women were aged 30-39, lived in rural areas, and had a high school education level. Early sexual intercourse (under 18 years old) (OR = 4.2, AOR = 3.8) and sexual activity during menstruation (OR = 5.4, AOR = 5.2) were identified as risk factors for non-specific vaginitis.Conclusion: The prevalence of non-specific vaginitis was 37.6%. Sexual behavior factors are associated with non-specific vaginitis.
Keywords: Non-specific vaginitis; associated factors.